Ischemic Retinopathy and Neovascular Proliferation Secondary to Severe Head Injury - Muge Coban-Karatas; Rana Altan-Yaycioglu (Case Reports in Ophthalmological Medicine)
We report a case with severe head trauma and perforating globe injury in one eye and ischemic retinopathy and neovascular proliferation in the other eye. A 37-year-old male was brought to the emergency department after a motor vehicle accident with severe maxillofacial trauma. Ophthalmic examination revealed hematoma of the left eyelids as well as traumatic rupture and disorganization of the left globe. On the right eye, anterior segment and fundoscopic examination were normal. Primary globe repair was performed. At postoperative one-month visit, the right eye revealed no pathology of the optic disc and macula but severe neovascularization in the temporal peripheral retina. The patient was diagnosed as ischemic retinopathy and neovascular proliferation due to head trauma.